Quantitative evaluation of waste sorting management policies in China’s major cities based on the PMC index model - Xu, Jiangtao; Zhang, Zaisheng; Xu, Yanqing; Liu, Li; Pei, Tong (Frontiers in Environmental Science, 2023)
Municipal Solid Waste governance in China entered a new phase in March 2017 when the Chinese government began requiring major cities to enforce waste sorting as well as to develop a system of laws, regulations, and standards regarding waste sorting. This study used text mining and the Policy Modeling Consistency (PMC) Index model to develop an evaluation system of Municipal Solid Waste sorting management policies that included 10 first-level variables and 51 second-level variables to quantitatively evaluate the texts of waste sorting management policies in 11 major cities, and then the PMC surface of policy texts was constructed to analyze the strengths and weaknesses of individual policies according to the PMC index values. The results revealed that there were no excellent level or bad level policies among the 11 policies, with an average PMC index value of 7.71. Overall, the 11 policy texts all set out clear goals and programs in accordance with local conditions. However, different policies differ significantly in various indicators, especially in the variables of policy content, policy function, policy evaluation,restriction and incentives. This study provides a new perspective for the policy analysis of waste sorting manangement in China’s major cities, and offers proposals for the optimization of waste sorting management policies